The Problems with Apartments and Land Acquisition in Australia for Foreign Citizens (An International Overview) - Glompy, Margaret (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2023)
This research aims to determine the quality of apartment buildings in Australia which are now in the spotlight, after the last case experienced by residents of the Mascot Towers complex in Sydney. They had to be evacuated because of cracks in the building. Previously also in Sydney, about 3,000 residents of the Opal Towers apartment were evacuated due to the collapse of the building's supporting beams. This research is a qualitative research in which the researchers themselves are engaged in the field as a key instrument. The results and discussion show that a number of apartment owners in other cities who were contacted explained that they are now worried that the structure of their apartment buildings is not safe to live in. They also had to pay for the damage themselves. One of them is John Grant, who owns an apartment in Canberra that he bought for 640,000 in 2011. Not long ago, cracks appeared that spread across the floor of the apartment parking lot. Grant said he had information that the crack could be repaired, but that the cost was estimated at 9 million. If this cost is to be borne by the owners of the apartments in the complex, each must pay 75,000. The conclusion in this study is that due to the inconvenience of existing apartments, apartment owners are now filing lawsuits against contractors, developers and designers of their apartment buildings.